SEMINAR PENGASUHAN POSITIF BAGI ORANGTUA KOMUNITAS GKII TENGGARONG, KUTAI KERTANEGARA KALIMANTAN TIMUR - Denrich Suryadi; Agustina Agustina; Widya Risnawaty (PROSIDING SERINA, 2021)
Loving parental care, proper discipline, and inculcation of positive life values provided by parents are supporting factors in preparing children to become healthy individuals. Safe, comfortable and positive parent-child interactions will form the basis for healthy child development. Parenting is about how children are raised in early life and beyond will affect brain development, language, social skills, emotion regulation, mental and physical health, health-risk behaviors and the ability to cope with the various events of life. Therefore, parenting is an important and potential target of preventive intervention.To prevent the impact of the increasing number of problems, the Gereja Kemah Injil Indonesia (GKII) Tenggarong respond to the requests and needs of families to provide psychoeducation about families. In addition, the Kutai Kertanagara area will become the capital of the Indonesia new government, so it is necessary to take preventive steps in accepting a new development for its people, especially the family as the smallest and most important community unit. The situation analysis of the needs of GKII Tenggarong regarding the issue of parenting for the millennial generation. As previously noted, positive parenting is the right parenting method for millennial generation because it emphasizes giving positive discipline, appropriate consequences, attachment factors and healthy communication patterns between parents and children. This psychoeducation activity went well and was attended by 42 parents for 2 hours on Saturday, January 23, 2020 via Zoom and was able to provide education and new understanding about the implementation of positive parenting.